Implications of weeds of genus euphorbia for crop production: a review - Tanveer,A. (2013)
The genus Euphorbia comprises about 2000 species ranging from annuals to trees, including C3, C4, and CAM species. Euphorbia species widely studied in agriculture includes E. antiquorum, E. carollata, E. dentata, E. dracunculoides, E. esula, E. geniculata, E. granulata, E. helioscopia, E. heterophylla, E. hierosolymitana, E. hirta, E. maculata, E. microphylla, E. nerifolia, E. piluifera, E. pulcherrima, E. royleana, E. supine, and E. thiamifolia. These species have been reported mainly in field crops/vegetables, orchards, pastures, and rangelands. Euphorbia plants may present allelopathic effect over desirable cereals, pulses, oilseeds, vegetables, forage plants, and nitrifying bacteria, posing a serious threat to livestock production on open range lands through the release of allelochemicals from roots, stems, leaves, and inflorescence in the rhizosphere. Leaves are reported to be more toxic than other plant parts. Competition of Euphorbia spp. against crop plants is the most important crop yield-limiting factor. The critical period for Euphorbia competition with crops is reported to take place between 17 to 70 days after emergence for most crops, depending on root development during the initial crop growth stage, crop height, tillering or branching capacity, whether weeds emerge at the same time as the crop or later after crop emergence; how quickly crop canopy develops and also on Euphorbia species. A yield reduction of 4-85% has been reported in field crops with different Euphorbia species and distinct occurrence densities. Euphorbia species decrease herbage production by 10 to 100% in pasture and rangelands, with many acting as natural insecticide, fungicide, nematidicide, immunopotentiator, or immunosuppressor.